Cost-based analysis of autonomous mobility services - Bösch, Patrick M.; Becker, Felix; Becker, Henrik; Axhausen, Kay W. (Transport policy, 2018)
Fast advances in autonomous driving technology trigger the question of suitable operational models for future autonomous vehicles. A key determinant of such operational models’ viability is the competitiveness of their cost structures. Using a comprehensive analysis of the respective cost structures, this research shows that public transportation (in its current form) will only remain economically competitive where demand can be bundled to larger units. In particular, this applies to dense urban areas, where public transportation can be offered at lower prices than autonomous taxis (even if pooled) and private cars. Wherever substantial bundling is not possible, shared and pooled vehicles serve travel demand more efficiently. Yet, in contrast to current wisdom, shared fleets may not be the most efficient alternative. Higher costs and more effort for vehicle cleaning could change the equation. Moreover, the results suggest that a substantial share of vehicles may remain in private possession and use due to their low variable costs. Even more than today, high fixed costs of private vehicles will continue to be accepted, given the various benefits of a private mobility robot. •Comprehensive cost analysis of different types of autonomous vehicles.•Market predictions for electrified and/or autonomous vehicles.•Private vehicle ownership will likely endure the rise of such new technologies.•Mass transit likely confined to dense urban areas.•Service costs to be main cost factors of shared autonomous vehicles.